Psychiatry researchers from the Council for Scientific and Technological Development - Souza, Gilmerson Prates; Sousa , Árlen Almeida Duarte de; Barbosa, Mariane Silveira; Magalhães, Marcelo José da Silva de; Maia, Janini Tatiane Lima Souza; Martelli Júnior, Hercílio (Bionorte, 2025)
The aim of this study was to describe the profile and scientific production of research fellows of the Council for Scientific and Technological Development in the psychiatry area. A cross-sectional, census and quantitative study was conducted. We created a database containing 541 researchers who were CNPq fellows in Medicine, of which 45 (8.31%) worked mainly in psychiatry. The evaluation included 45 researchers, majority male (n=35; 77.77%) and grants in category 2 (n=17; 37.77%). All researchers were distributed in four Brazilian states, with the Southeast region being the most prevalent (n=31; 68.88%). The researchers published 11,022 papers in scientific journals, with an average of 244.93 articles per researcher. Over their careers, the 45 researchers advised 734 scientific initiation students, 702 master’s degree students and 603 PhD students. The researchers in the field of psychiatry present a relevant scientific output from the quantitative and qualitative point of view.